2020
DOI: 10.3168/jds.2020-18317
|View full text |Cite
|
Sign up to set email alerts
|

Physical and economic comparison of pasture-based automatic and conventional milking systems

Abstract: Automatic milking systems (AMS) have the potential to increase dairy farm productivity and profitability; however, adoption rates, particularly in pasture-based systems, have been lower than expected. The objectives of this study were to compare the physical and economic performance of pasture-based AMS with conventional milking systems (CMS) and to identify gaps for improving AMS productivity and profitability. We used data from 14 AMS and 100 CMS located in the main Australian dairy regions and collected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Gargiulo et al [48] discussed in 2020 about the low adoption rate of AMS regardless of the increased possibility of productivity and profitability rates. Although his study results contest the research hypothesis, he concluded that CMS had similar results with the AMS in terms of human resource costs, income level and profitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gargiulo et al [48] discussed in 2020 about the low adoption rate of AMS regardless of the increased possibility of productivity and profitability rates. Although his study results contest the research hypothesis, he concluded that CMS had similar results with the AMS in terms of human resource costs, income level and profitability.…”
Section: Discussionmentioning
confidence: 99%
“…Although his study results contest the research hypothesis, he concluded that CMS had similar results with the AMS in terms of human resource costs, income level and profitability. The initial investment and maintenance costs entail greater cost of AMS [48]. Bijl et al discovered that the over-cost for AMS in the Netherlands were significantly lower [49] (pp.…”
Section: Discussionmentioning
confidence: 99%
“…This has positive practical implications if the RPM is used to calibrate remote sensing-captured data, as it simplifies the task. If we consider an average farm with an area of ≈150 ha [6] and 64 RPM readings/ha, the farmer will need to perform 9,600 readings to achieve good accuracy. From the duration per RPM reading recorded in the current work (2.2 s per reading), monitoring with the RPM across the whole farm will require 5.9 h. Anecdotal evidence from dairy farmers indicates that this task could require ≈3 h on average, suggesting that farmers would work with reduced numbers of steps as we recommend here, and therefore increased error.…”
Section: Discussionmentioning
confidence: 99%
“…As the annual pasture utilization (pasture ingested per cows per hectare) is positively associated with profitability [2,3], methods to increase this utilization should improve the overall farm business performance. In this regard, there is a substantial opportunity for most commercial farms to lift profitability, given the large gap between current and potential pasture utilization [4][5][6]. Accurate measurement and allocation of pasture can increase milk production by ≈10%, mainly by utilizing the pasture that otherwise would be wasted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out indicate that the farms that have AMS register greater quantity and better bacterial quality of milk produced, as well as saving labor [ 148 , 149 ]. In turn, these systems imply higher repair and maintenance costs, as well as the need for specialized staff [ 150 ]. A recent study conducted on a farm in the United Kingdom found that after installing an AMS, there was a 13% increase in yield and a 28% reduction in somatic cell count (SCC) [ 151 ], with variations depending on farms.…”
Section: Milk Production: From Rearing To Milkingmentioning
confidence: 99%